Case of oculo-auriculo-vertebral spectrum: rare clinical features. Issue 3 (3rd March 2021) - Khera, Daisy; Agarwal, Saurabh; Kumar, Prawin; Singh, Kuldeep
Abstract : A 2-month-old boy presented to us with bilateral microtia, left lower motor neuron facial palsy, micrognathia, hemivertebra, bifid rib, bifid thumb and absent/hypoplastic right-sided depressor anguli oris. He had bilateral external auditory canal atresia, although response to loud sound was present. Brain stem evoked response audiometry (BERA) was advised at 3 months of age. Karyotype was normal. We diagnosed him as a case of oculo-auriculo-vertebral spectrum. Child was discharged on request by the family with the plan for bone-anchored hearing aid after BERA and plan for pinna and ear canal reconstruction at a later age but child did not come for any follow-up visit. On telephonic enquiry, it was found that he is thriving well but has developmental delay including speech delay. We conclude that children presenting with external ear abnormalities should be screened for multiple congenital anomalies so that a multidisciplinary approach to management can be planned.